2015
DOI: 10.1136/bmjopen-2015-009446
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the community-specific prevalence of and factors associated with substance use and misuse among Rural and Urban adolescents: a cross-sectional analysis in Bosnia and Herzegovina

Abstract: ObjectiveThe community of residence (ie, urban vs rural) is one of the known factors of influence on substance use and misuse (SUM). The aim of this study was to explore the community-specific prevalence of SUM and the associations that exist between scholastic, familial, sports and sociodemographic factors with SUM in adolescents from Bosnia and Herzegovina.MethodsIn this cross-sectional study, which was completed between November and December 2014, the participants were 957 adolescents (aged 17 to 18 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 28 publications
5
41
1
Order By: Relevance
“…Our findings are therefore in accordance with the results of previous cross-sectional studies performed with adolescents of a similar age, which repeatedly reported lower educational achievement among children who smoke. 7 18 27 Although there is a general consensus on the negative associations between smoking and performance in school, the mechanisms that lead to these associations are still controversial. Some authors highlight the negative effects of smoking on cognitive capacities, and consequently poorer learning capabilities, as a result of cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are therefore in accordance with the results of previous cross-sectional studies performed with adolescents of a similar age, which repeatedly reported lower educational achievement among children who smoke. 7 18 27 Although there is a general consensus on the negative associations between smoking and performance in school, the mechanisms that lead to these associations are still controversial. Some authors highlight the negative effects of smoking on cognitive capacities, and consequently poorer learning capabilities, as a result of cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing the certain religiously-inherited boundaries toward certain substances (e.g., alcohol with regard to Islam), and/or traditional perception of some SUM behaviors (i.e., tobacco smoking as a part of “eastern” and Arab culture), differences in SUM behaviors and factors associated to SUM among adolescents can be expected. Indeed, when observing the previous studies that investigated exclusively one ethnicity done on Croatian [1] and Bosniak adolescents [2,5] from Bosnia and Herzegovina, several conclusions can be made. First, Croatian boys consume alcohol to greater extent than Bosniaks (47% and 40%, respectively).…”
Section: Introductionmentioning
confidence: 96%
“…In brief, daily smoking in Europe ranges mostly between 10%–20%, while 20% of adolescents in Bosnia and Herzegovina smoke on a daily basis [3,4]. Thus, Bosnia and Herzegovina, together with Hungary (18% daily smokers), Belgium (18%), and Austria (20%), is among the European countries with the highest prevalence of adolescent smoking [5,6]. Not surprisingly, high prevalence of smoking is recognized as one of the most important risk factors for high risk of morbidity and mortality related to cardiovascular diseases in the country [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a significant decrease in tobacco consumption has been observed globally from 2002 to 2010, this trend is still lagging behind in Eastern Europe (42). At the same time, living in the urban environment should be considered as a higher risk factor for substances use, especially in females (43).…”
Section: Discussionmentioning
confidence: 99%